Skal vi have lærebøger til musikundervisningen? En rundbordsdiskussion - Nielsen, Lars (Modspil, 1979)
Deltagere: Karsten Tanggaard, Kirsten Toksvig, Steen Bülow-Hansen, Annette Juul-Hansen, Lars Nielsen